Groundswell in Bengal in the 1940s - Dasgupta, Atis K. (Atis Kumar), 1945- (Calcutta : National Book Agency, 1995)
Chiefly on the 1946-1947 peasant movement in Bengal for the larger share of produce.
Includes bibliographical references (p. 92-[95]).
Keywords: Insurgency -- India -- Bengal -- History; Peasant uprisings -- India -- Bengal -- History; Bengal (India) -- History